The Sociology of Religion: Some Areas of Theoretical Potential - Schneider, Louis (Sociological analysis, 1970)
Five “areas” where there seems to be potential for theoretical progress in the sociology of religion are presented. One area has to do with accurately aggregating or putting together the elements of the “religious” in order to facilitate possible continuation of sophisticated functional and interchange analysis. Another area is suggested by processes of personification and mythologization occurring in economic and political spheres often not connected with religion. A third area bears on the sociology of religion in relation to general cultural theory; and a fourth on religion as “dialectical.” Fifthly, while close attention to more or less comprehensive views of religion for their sociological suggestiveness does not constitute an “area” it can still be theoretically most stimulating and is loosely referred to as an “area”.